Analysis of the possibility of a parallel resonant circuit in RHPP Bajina Bašta - Dilparic Cakić, Milica; Kovačević, Branka (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
The pumps in RHPP Bajina Bašta are started via a static frequency converter (SFC). This resulted in increased level of higher harmonics within the RHPP. However, it was not known whether the operation of this SFP could endanger the consumers supplied from the mentioned RHPP via the distribution transformer. For this purpose, it is necessary to check the possibilities of the existence of a parallel resonant circuit, both in the RHPP itself, and in the part of the distribution network that was of interest. Analyzes were performed in the linear simulation model created in the DIgSILENT PowerFactory software package. The simulation model was created so that it corresponds to the state of minimum load of the distribution area supplied by TS Metaljka. Also, several variants were analyzed in TS Đurići (depending on the number of motor engines in operation). The results show the existence of parallel resonant circuit in the vicinity of the 13th harmonic at the level of 10 kV busbars in TS Metaljka, while its existence was not identified at the transmission system busbar, which is in accordance with the measurements.